A Comprehensive Analysis of Bandwidth and Size for Four-Types of Series-Combined Transformer-Based Doherty Output Networks: Theory and Examples - Seokchul Lee; John D. Cressler (IEEE Access, 2025)
This paper presents theory-driven design guidelines for four types of series-combined transformer (SCT)-based Doherty output matching networks to maximize bandwidth (BW). Novel and intuitive methods were proposed for analyzing the series Doherty combiners. Compared with prior analyses relying solely on ideal or insufficient models, this study systematically derives closed-form design equations based on non-ideal transformer-based practical circuit models. Doherty load modulation was clearly demonstrated for all four types using two combinations of SCT models and four capacitor configurations. Furthermore, the design parameters were simplified, and the equations were validated for both symmetrical and asymmetrical SCTs. To estimate the maximum achievable BW and identify the key design factors, four design examples of each type were compared using circuit simulations and numerical analysis. A clear trend observed across all four types is that a higher magnetic coupling coefficient results in a larger fractional BW. It is also demonstrated that the distinct “sweet spots” for the four types, when maximizing BW, depend mainly on only 2 or 3 variables, including turn ratios and/or self-inductances. SCT sizes were compared based on the sum of the two transformer dimensions. To validate the circuit model, a design example was built through a detailed procedure as the best practice, and a layout-based full-EM structure achieved close-to-theoretical BW. For further verification, four SCT-based Doherty power amplifiers were simulated and compared.